A study on the leasing industry in Malaysia / Fatimah Bee Mohd Kassim - Mohd Kassim, Fatimah Bee (1973)
Leasing industry in Malaysia has been operated for the past two decades and it has shown a steady growth. Nevertheless, its growth is affected by many factors. This paper is prepared to analyse few economic variables that might have an impact on leasing industry growth. It is a study using secondary data, which were obtained from Bank Negara and Equipment Leasing Association of Malaysia with the objective of analysing the types of equipments and industry sectors involve in leasing business. The discussion begins with an explanation of the theoretical framework for the analysis and the basic multiple regression is used to arrive to the ultimate results. In the findings, the interest rates appear to be significantly related to the total cost of assets involve in leasing business. This is proved by correlation which shows the relationship between the interest rates and the value for leasing businesses.